The influence of biocalcification on soil-cement interlocking block compressive strength - Sada Yoosathaporn (2018)
© 2015, FAC UNIV SCIENCES AGRONOMIQUES GEMBLOUX. All rights reserved. Description of the subject. Soil-cement interlocking block is used as the building block for many civil structures in Thailand. The addition of many alternative materials into interlocking block in order to improve compressive strength has been reported. However, there is currently no report on the influence of application of biocalcification or microbiologically induced calcite precipitation (MICP) on interlocking block compressive strength. Objectives. This study aimed to investigate the effect of biocalcification on compressive strength of soil-cement interlocking block. Method. Soil bacterium, Bacillus pasteurii KCTC 3558, and Effective Microorganisms (EM) were added into interlocking block before molding as the replacement of mixing water. The change of compressive strength in interlocking block at 3, 7, 14 and 28 days of incubation was determined. Results. At 28 days, the compressive strength of interlocking block supplemented with B. pasteurii KCTC 3558 and 5% EM were 7.38% and 9.79% significantly higher than control. Calcium carbonate crystals were also observed under scanning electron microscope which suggested that an increased compressive strength of interlocking block was caused by biocalcification. Conclusions. Our results showed that microbiologically induced calcite precipitation could help increasing the compressive strength of soil-cement interlocking block.